Relationships among streptococci from the mitis group, misidentified as Streptococcus pneumoniae - Sadowy, Ewa (Eur J Clin Microbiol Infect Dis, 2020)
The aim of our study was to investigate phenotypic and genotypic features of streptococci misidentified (misID) as Streptococcus pneumoniae, obtained over 20 years from hospital patients in Poland. Sixty-three isolates demonstrating microbiological features typical for pneumococci (optochin susceptibility and/or bile solubility) were investigated by phenotypic tests, lytA and 16S rRNA gene polymorphism and whole-genome sequencing (WGS). All isolates had a 6-bp deletion in the lytA 3′ terminus, characteristic for Mitis streptococc and all but two isolates lacked the pneumococcal signature cytosine at nucleotide position 203 in the 16S rRNA genes. The counterparts of psaA and ply were present in 100% and 81.0% of isolates, respectively; the spn9802 and spn9828 loci were characteristic for 49.2% and 38.1% of isolates, respectively. Phylogenetic trees and networks, based on the multilocus sequence analysis (MLSA) scheme, ribosomal multilocus sequence typing (rMLST) scheme and core-genome analysis, clearly separated investigated isolates from S. pneumoniae and demonstrated the polyclonal character of misID streptococci, associated with the Streptococcus pseudopneumoniae and Streptococcus mitis groups. While the S. pseudopneumoniae clade was relatively well defined in all three analyses, only the core-genome analysis revealed the presence of another cluster comprising a fraction of misID streptococci and a strain proposed elsewhere as a representative of a novel species in the Mitis group. Our findings point to complex phylogenetic and taxonomic relationships among S. mitis-like bacteria and support the notion that this group may in fact consist of several distinct species. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10096-020-03916-6) contains supplementary material, which is available to authorized users.